Pengaruh Kepribadian Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Pusat Statistik Kabupaten Lombok Tengah - Tira Satika; Thatok Asmony; Sarifudin Serip (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The study aims to determine the effect of personality and work motivation on employee performance at Badan Pusat Statistik office in Central Lombok Regency. The data collection method used is the census method using primary data collected directly from the respondents using a questionnaire. The type of research used in this research is associative research with a quantitative approach. The population number in the study was 33 respondents. The analytical tool used is multiple linear regression analysis using SPSS version 25. The results of the analysis show that: (1) Personality has a positive and significant effect on employee performance, (2) Work motivation has a positive and significant effect on employee performance.